The effect of high-intensity interval training on hematological variables and lipid profiles in team game athletes - Sarkar, S.; Bandyopadhyay, A.; Datta, G.; Dey, S. K. (Trends in Sport Sciences, 2023)
Introduction. High-intensity interval training (HIIT) has gained popularity as a quick and effective way to exercise, and the training consists of a short burst of intense exercise that precedes a period of rest or low intensity exercise.